Analisis Teori Hukum Positif dan Teori Sistem Hukum terhadap Perbuatan Tidak Melaporkan Pelaku Penyalahgunaan Narkotika - Andry Yosep Manalu; Idham Idham; Erniyanti Erniyanti (Penerbit Goodwood, 2022)
Purpose: The purpose of writing this journal is to find out the legal consequences for parent's who do not report narcotics addicts to law enforcement officials, and to know law enforcement efforts in increasing parent's awareness to report narcotics addicts. Methodology: The method used is a normative approach, namely through library research, and an empirical approach, namely through field research by conducting a series of interviews with respondents and informants to obtain field data. Result: The results of the study show that, due to legal consequences for parent's who do not report narcotics addicts to the authorities, that person can be subject to criminal sanctions in the form of imprisonment for a maximum of 6 (six) months or a fine of up to Rp. 1,000,000.00 (one million rupiah). Law enforcement efforts in increasing parent's awareness to report narcotics addicts in Batam City are repressive actions by strictly enforcing the law for anyone involved in narcotics crimes, preventive actions through socialization and working with village officials to increase supervision of narcotics circulation, and persuasive actions by providing formal and non-formal education to the wider community to stay away from and work together to eradicate narcotics which can damage the future of the nation's generation.